2012
DOI: 10.2106/jbjs.k.00874
|View full text |Cite
|
Sign up to set email alerts
|

Calcific Periarthritis: More Than a Shoulder Problem

Abstract: Of twelve histologically verified cases of calcific periarthritis adjacent to joints other than the shoulder, in only one patient (toe) was the preoperative clinical diagnosis accurate, which signals the need for greater awareness of this entity as a differential diagnostic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Clinically, patients present with pain, localised swelling, erythema, tenderness and restricted range of motion [10,15,16]. Even without treatment, the majority of patients report a reduction in symptoms within 4-7 days after the acute onset of pain and resolution in 3-4 weeks [4,17].…”
Section: Clinical Presentation Course and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, patients present with pain, localised swelling, erythema, tenderness and restricted range of motion [10,15,16]. Even without treatment, the majority of patients report a reduction in symptoms within 4-7 days after the acute onset of pain and resolution in 3-4 weeks [4,17].…”
Section: Clinical Presentation Course and Managementmentioning
confidence: 99%
“…Pathological examination demonstrates deposition of calcific material into psammoma-like bodies, which is surrounded by extensive inflammatory cells, in particular, neutrophils [25,26]. The composition of the calcific deposits on electron microscopy is controversial [15]. Previously, studies have reported the deposits to consist of calcium hydroxyapatite; hence, the term hydroxyapatite deposition disease has been used to describe the underlying disease process of calcific periarthritis and calcific tendonitis [13,[27][28][29][30].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly described area of involvement is the great toe, either presenting medial to the first metatarsophalangeal joint or at the flexor hallucis brevis tendon just proximal to the hallucal sesamoids (Figure 16) [4, 90]. When CADD involves the flexor hallucis brevis, it typically presents with focal tenderness along the plantar forefoot near the first metatarsal head and can be mistaken for hallucal sesamoiditis [4].…”
Section: Locationsmentioning
confidence: 99%
“…CADD of the first metatarsophalangeal joint can mimic gout arthropathy. However, slightly younger age distribution, female gender predilection, and normal serum urate levels can help distinguish calcium deposits of CADD from gouty tophus [90]. Less common sites of involvement described include the peroneus longus at the peroneal groove, navicular insertion of the tibialis posterior, and second through fifth metatarsophalangeal joints [9092].…”
Section: Locationsmentioning
confidence: 99%